Answer:
attached below is the prove
Step-by-step explanation:
In order to prove the expression for coefficient b[tex]_{2}[/tex] we have to find b[tex]_{0}[/tex] and b[tex]_{1}[/tex]
F(x) = [tex]b_{0} + b_{1} ( x - x_{0} ) + b_{2} ( x - x_{0} ) (x - x_{1} )[/tex]
i) Determine b[tex]_{0}[/tex]
at x = x[tex]_{0}[/tex]
b[tex]_{0}[/tex] = f(x[tex]_{0}[/tex] )
ii) Determine b[tex]_{1}[/tex]
at x = [tex]x_{1}[/tex]
f ([tex]x_{1}[/tex]) = f ([tex]x_{0}[/tex] ) + b[tex]_{1}[/tex] [tex](x_{1} - x_{0} )[/tex] + 0
[tex]b_{1} = \frac{f(x_{1} )-f(x_{0} )}{(x_{1}-x_{0} ) }[/tex]
prove of the expression for the coefficient B2 in the quadratic interpolation
attached below is the detailed prove